AFRICA BUILD: Creating Web 2.0 Communities of Biomedical Researchers - Jimenez-Castellanos, Ana; Perrin, Caroline; Ramirez-Robles, Maximo; Ingelbeen, Brecht; Maojo, Victor (Journal of Health Informatics in Africa, 2013)
Background and Purpose: Health researchers need access to continuing education and specialized advice to improve the quality, efficiency and accessibility of health systems. The creation of communities of researchers can provide the information necessary for their daily work in addition to strengthening the links between researchers. In this context, Web 2.0 technologies can facilitate the establishment of these communities.The AFRICA BUILD project aims to promote health research through the creation of virtual communities of health researchers, educators and practitioners, and the use of Information and Communication Technologies. This paper highlights the main findings and challenges found in the development of these communities.Methods: We have developed a social platform, the AFRICA BUILD Portal (ABP), which integrates health research related didactic contents and resources, as well as tools that facilitate collaboration. This portal has been developed following three principles: (i) use of free and open source tools, (ii) adaptation of these tools to low bandwidth connections, and (iii) creation of a Euro-African community of developers for the sustainability of the ABP.Results: Several communities of users were initiated within the ABP, mainly structured in three types according to: the organization or country to which they belong, the specific area they are working in, and researchers from two pilots courses on HIV/AIDS and Reproductive Health Research.Conclusions: Project partners and associates, who form several communities of users, currently use the ABP. The main challenges faced in the creation of these communities are: the language, a need for facilitators for the discussions and interactions, and the motivation of some members to actively participate and contribute in exchanges. In future steps, we plan to develop new functionalities within the ABP and disseminate the platform to the biomedical scientific community in Africa, fostering the creation of African communities of biomedical researchers.Keywords: Community Networks, Health Research, Social Media